Neuropsychiatric manifestations in patient with normal pressure hydrocephalus improved with therapeutic lumbar tapping - Padma, Kumari; ., Chandini; A., Siddharth Shetty; T., safeekh A.; S., Raghavendra B. (International Journal of Research in Medical Sciences, 2019)
Normal pressure hydrocephalus is a communicating hydrocephalus without evident obstruction of the normal pathway of CSF flow. Normal-pressure hydrocephalus is a common cause of reversible dementia and it can also present with various psychiatric symptoms. A 76-year old man was brought to psychiatry OPD with history suggestive of decreased need for sleep for 8 days, disinhibited behaviour, increased libido, increased activity and increased talk for 4 days. On examination patient was noticed to be having increased psychomotor activity with increased talk, mood reported to be happy with elated affect, no content or perceptual disturbances were elicited. Cognitive functions were within normal limits. Personal and social judgement was impaired with grade 0 insight. General physical and systematic examinations were within normal limits. MRI reports showed ventricular enlargement suggestive of normal pressure hydrocephalus. Patient underwent diagnostic and therapeutic lumbar tapping. There was significant improvement in patient’s behavioural symptoms following therapeutic lumbar tapping. Therapeutic lumbar tapping in this case of normal pressure hydrocephalus was effective in the management of manic symptoms. Early identification of organic cause in late onset psychiatric disorders is necessary. Prompt intervention of the organic cause was effective in the management of manic symptoms.